ANALYSIS OF THE LANDSCAPE AND ECOLOGICAL STATE OF THE ATYRAU REGION - Tokbergenova, A. A.; Mussagaliyeva, A. N.; Ryskeldiyeva, A. M; Akmoldayeva, B. K. (ЗКАТУ им. Жангир хана, 2024)
The arid landscape of the Caspian Lowland (Atyrau region) is a very fragile natural geosystem of interrelated components. The transformation of arid landscapes due to the scale of anthropogenic impact leads to desertification processes. The research is devoted to the analysis of the landscapeecological state of the Atyrau region, characterized by arid landscapes subject to significant anthropogenic impact. The relevance of the study is due to the need to develop effective methods for monitoring and managing natural resources for the sustainable development of the region. The purpose of the study is to assess the state of natural and anthropogenically disturbed landscapes, identify the main factors of their transformation and offer recommendations for improving the ecological situation of the region. Research methods included the use of a system of general scientific methods, such as landscape analysis, synthesis and cartographic tools. The main materials of the study consisted of landscape and other maps of the territory, as well as statistical data. The research results showed the significant influence of oil production, agriculture and other anthropogenic factors on the ecological state of the region’s landscapes. The main problems associated with soil, water and air pollution, vegetation degradation and erosion processes have been identified. Measures have been proposed to improve the landscape and ecological condition of territories exposed to anthropogenic activities.
Tokbergenova, A. A. Аnalysis of the landscape and ecological state of the atyrau region / A. A. Tokbergenova, A. N. Mussagaliyeva, A. M. Ryskeldiyeva, B. K. Akmoldayeva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - № 4-2 (77). Ч. ІІ. - Р. 145-157 (Uralsk).
Keywords: arid landscapes; technogenic impact; petroleum products; agricultural impact; ecological state.; научный журнал; зкату